Pengaruh kemudahan penggunaan, kepercayaan konsumen dan kreativitas iklan terhadap minat beli konsumen online-shop - Khusnul Khotimah; Febriansyah Febriansyah (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2018)
This study aims to determine the effect of ease of use, consumer trust and advertising creativity on consumer buying interest in online buying and selling sites, Bukalapak.com. This study uses a quantitative approach by conducting surveys and tests on 115 respondents. In the data analysis technique used is multiple linear regression analysis. The testing technique using the help of the SPSS 22 system. The results of hypothesis testing (t test) which shows that the variables of consumer trust and advertising creativity have a significant effect on the performance variable. But the ease of use variable has no significant effect on performance variables. The conclusion of this study is that consumer trust and advertising creativity are the most dominant variables for buying interest.